Synthesis of Functionalized Cannabilactones - Liu, Yingpeng; Ho, Thanh C.; Baradwan, Mohammed; Pascual Lopez-Alberca, Maria; Iliopoulos-Tsoutsouvas, Christos; Nikas, Spyros P.; Makriyannis, Alexandros (Molecules (Basel, Switzerland), 2020)
A new approach to synthesize cannabilactones using Suzuki cross-coupling reaction followed by one-step demethylation-cyclization is presented. The two key cannabilactone prototypes AM1710 and AM1714 were obtained selectively in high overall yields and in a lesser number of synthetic steps when compared to our earlier synthesis. The new approach expedited the synthesis of cannabilactone analogs with structural modifications at the four potential pharmacophoric regions.